A family with spondyloepimetaphyseal dwarfism: a 'new' dysplasia or Kniest disease with autosomal recessive inheritance?. Issue 10 (October 1987) - Farag, T I; Al-Awadi, S A; Hunt, M C; Satyanath, S; Zahran, M; Usha, R; Uma, R
Abstract : We present an Arab family with some features of Kniest disease. The proband was a six year old boy with rhizomelic short limbed dwarfism, 'dish-like' facies, cleft palate, deafness, and camptodactyly. Most radiological changes were compatible with Kniest disease. Two younger sibs, similarly affected, had died at a few months old, and the pedigree shows strong evidence of autosomal recessive inheritance, unlike previously reported cases of Kniest disease which have shown autosomal dominant inheritance.